Etika Perataan Laba dari Perspektif Akuntansi Syariah - S. Suwandi (Akuntabilitas, 2017)
This study aims to find out the ethics of income smoothing seen from the perspective of Islamic religion because the action of income smoothing (smoothing earnings) is an action that can mislead the users of financial statements by presenting information that is not accurate, and sometimes even the cause of illegal acts,  accountants educators, managers, and Ustadz believes it is an act that is prohibited by religion because the nature of the work it does is a mandate, whether it is worldly from its superior or business owner, or worldly from Allah SWT who will be held accountable for the work he does. Implementation of honest and trustworthy in work among others is to not take something that is not his right. The reason of the selection of informants is because all three have a relationship to the practice of Income Statement and all informants argue the same. The performance of unstable financial statements or decreased financial performance is less good, it tends to trigger the behavior of managers to perform unethical actions, so to give the impression of good company performance needs to be done income smoothing, income smoothing can be done by manipulating variables -variables (accounting) pseudo or by conducting real transactions, or can also be done by choosing an accounting method in accordance with the wishes of management.